Successfully dating rock art in Southern Africa using improved sampling methods and new characterization and pretreatment protocols - Brock, Fiona; Bonneau, A.; Staff, R. A.; Higham, T.; Pearce, D. G.; Mitchell, P. J. (University of Arizona, 2016)
Worldwide, dating rock art is difficult to achieve because of the frequent lack of datable material and the difficulty of removing contamination from samples. Our research aimed to select the paints that would be the most likely to be successfully radiocarbon dated and to estimate the quantity of paint needed depending on the nature of the paint and the weathering and alteration products associated with it. To achieve this aim, a two-step sampling strategy, coupled with a multi-instrument characterization (including SEM-EDS, Raman spectroscopy, and FTIR spectroscopy analysis) and a modified acid-base-acid (ABA) pretreatment, was created. In total, 41 samples were dated from 14 sites in three separate regions of southern Africa. These novel protocols ensure that the 14C chronology produced was robust and could also be subsequently applied to different regions with possible variations in paint preparation, geology, weathering conditions, and contaminants.
©2016 University of Arizona. This is the Author Accepted Manuscript. Please refer to any applicable publisher terms of use.
Keywords: Sample selection; Rock art dating; C AMS dating; Pretreatment; Paint characterization